La Nebulización y su influencia en el tratamiento de la bronquiolitis aguda en niños menores de 2 años ingresados en la unidad de pediatría del Hospital Seguro Social. Babahoyo. Los Ríos. Periodo mayo - septiembre 2019. - Peralta Murillo, Ahiliz Del Pilar (2019)
This research work was carried out with the purpose of determining the influence of the nebulization in the treatment of acute bronchiolitis of children admitted to the Pediatric Unit of the Babahoyo Canton Social Security Hospital, so to develop the research used the empirical methodology based on scientific research and the type of research that was used is field, descriptive, exploratory and transversal, to determine the study sample of this research no formula was used because an intentional sampling was applied where They used inclusion and exclusion criteria. A proposal was also elaborated that consists of giving talks to the parents on how to avoid being infected by this respiratory infection and the importance of following the pulling with fogging because it was feasible for a quick improvement.